Providing a Model for Implementing an Effective Internal Control System in Banks - Nazarian, Abdulhamid; Saeedi, Ali; Joola, Jafar (Future of Work and Digital Management Journal, 2025)
The purpose of this research was to propose a model for implementing an effective internal control system in banks. Accordingly, from the perspective of its objective, this is an applied study, because in addition to its informative and scientific aspects, it also has practical implications for various companies and organizations, especially banks. Considering the purpose and nature of the study, the research method is qualitative. Furthermore, since this research aims to design a model, it is exploratory in nature. The results showed that the final factors identified after the thematic analysis and data analysis stage include: organizational and structural barriers (deficiency in organizational structure, shortage of organizational resources, and weak organizational culture), legal and regulatory barriers (deficiency in laws and regulations, supervisory challenges, and compliance issues), technological and informational barriers (deficiency in technology infrastructure, information management challenges, and automation issues), human and skill-related barriers (lack of skills and knowledge, deficiency in training and development, and motivational and behavioral issues), process and operational barriers (deficiency in process design, implementation challenges, and supervision and control issues), and environmental and external barriers (economic impacts, competitive challenges, and technological and innovation influences).